The Gift :How I gave away a Kidney and got richer at heart - Kochouseph Chittilappilly (Rupa Publication, 2016)
Kochouseph Chittilappilly, a successful industrialist and one of the leading names in business and philanthropy in Kerala, was sixty years old when he decided to take an unusual, even controversial step. Moved by the plight of a close relative, Chittilappilly decided to donate his kidney to a poor truck driver-a stranger. The Gift is Chittilappilly's inspirational story as he journeyed on the path to achieve his objective. He describes why he took this decision; the various objections from family members, business associates and society at large that he had to deal with; the medical and ethical checks and balances he had to tick off; and the final deep sense of satisfaction he derived from having started a whole chain of voluntary organ donation in the state by his momentous act. The Gift not only exposes the glaring ignorance about organ donation in India but also educates the reader about it by providing excellent insight into the personal, medical and legal aspects of being a donor. Simply told and inspiring, this unique story needs to be read and dwelled upon by every individual.